2009
DOI: 10.1007/s00428-009-0813-z
|View full text |Cite
|
Sign up to set email alerts
|

A combined histologic and molecular approach identifies three groups of gastric cancer with different prognosis

Abstract: The limited prognostic value of currently used histologic classifications of gastric cancer and their failure to account for the complexity of the disease as revealed by more recent investigations prompted a combined reinvestigation of histologic, molecular, and clinicopathologic patterns in 294 extensively sampled, invasive gastric cancers representing all main histotypes and stages of the disease and followed for a median of 150 months. Among histologic parameters tested, only cellular atypia, angio-lympho- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 46 publications
5
46
0
1
Order By: Relevance
“…Their histopathological and clinicopathological patterns have already been described [25]; 2 of the original 294 cases had to be excluded because there was no remaining tumor tissue in the paraffin block. No antiblastic therapy had been administered.…”
Section: Case Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their histopathological and clinicopathological patterns have already been described [25]; 2 of the original 294 cases had to be excluded because there was no remaining tumor tissue in the paraffin block. No antiblastic therapy had been administered.…”
Section: Case Seriesmentioning
confidence: 99%
“…In parallel investigations, several histological types and subtypes of prognostic value have been identified [19][20][21][22][23] that showed correlation with number and severity of genomic alterations [24] and permitted the development of a simple grading system, predictive of patient survival [25]. The system proved highly effective for a substantial proportion (about 30 %) of tumors fitting in the low-or high-grade groups, although leaving the intermediate-grade group largely unpredictable [26].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to colorectal MC, gastric MC is also associated with MUC2 overexpression [86,87]. Also, a higher rate of MSI is found in MC when compared with NMC (average of 14% versus 11%, RR 1.51, 95% CI 1.03-2.21; supplementary material, Figure S2) [86,[88][89][90][91]. Similar to CRC, MSI has been associated with a better prognosis in gastric carcinoma [92,93].…”
Section: Mucinous Gastric Carcinomamentioning
confidence: 99%
“…HER-2 overexpression and ERBB2 gene amplification are less common in MC than in NMC (1% versus 6%) [86,94]. A higher rate of 18qLOH, which is associated with adverse outcome, has been reported for gastric MC compared with NMC (52% versus 21%) [89]. Expression of PTEN seems to be less altered in gastric MC, compared with NMC; Kang et al found that 27% of NMCs displayed loss of PTEN whereas none of the MCs did [95].…”
Section: Mucinous Gastric Carcinomamentioning
confidence: 99%
“…The 2012 Update of the Consensus Statement from the International Mesothelioma Interest Group guidelines recognized difficulties with pattern recognition in small biopsies, and recommended using three main histological types (epithelioid, sarcomatoid, biphasic) with pattern descriptions in medical records, if possible [13]. Histological subtyping/patterns in many carcinomas correlate with patients' clinicopathological characteristics [17][18][19][20][21][22]. A reclassification proposal for resectioned lung adenocarcinoma specimens has even proposed reporting different patterns by 5% increments, based on predominant histology, as these patterns closely correlate to molecular and genetic characteristics and, more importantly, prognosis [23].…”
Section: Discussionmentioning
confidence: 99%